Understanding English Teachers’ Engagement in Professional Learning Communities for TPACK Reconstruction - Fadlilah, Sayyidatul; Yuliasri, Issy; Fitriati, Sri Wuli (Indonesian Journal of EFL and Linguistics, 2025)
This study examines the role of English teachers in Professional Learning Communities (PLCs) as they develop their Technological Pedagogical Content Knowledge (TPACK) within the context of cultural and religious norms in madrasahs in Semarang City, Indonesia. Using a qualitative ethnographic case study methodology, the data were collected through observations, questionnaires, and field notes to demonstrate teachers' behavioural, emotional, and cognitive engagement. The study consisted of 50 in-service English teachers from thirty Islamic junior high schools serving varying educational backgrounds and professional learning experiences. The findings suggest, using Fredricks et al.'s multidimensional framework on engagement, that the teachers were very engaged behaviourally when we measured their attendance, participation, and attempts to use technology in their classrooms. Emotionally, the teachers exhibited excitement, curiosity, key details, engagement, pride, and self-efficacy, which led them to feel connected to the PLC and motivated to experiment with different instructional practices. Cognitively, the teachers engaged in reflective practices, planning with goals, problem-solving, and pedagogically integrating technology with content. This study highlights that PLCs can be a formidable vehicle for collaborative professional growth, helping English teachers develop their technological teaching capacity and pedagogically innovate while maintaining their cultural and religious nuance. This study also highlights that TPACK reconstruction involves a process of continually engaging in multidimensional, ongoing interactions to be effectively reconstructed in a relevant context.